(untitled) (Itinera, 2016)
This paper recreates some of the most relevant theoretical moments of the development of philosophical analysis of issues about food, nutrition, gastronomy and cuisine, in particular: (1) cognitive approach proposed by Carolyn Korsmeyer; (2) the reflection of Jèssica Jaques, who has been focusing on two aspects: what she called “Gustatory Philosophy” and “Aesthetics of Gastronomy”; (3) the main theses proposed by Nicola Perullo, who has introduced in Italy the aesthetics of food intended as a philosophical discipline.